Implementing Project-Based Learning in Writing Course: A Case Study in the ELT - Fatmawati, Ayu (Prosiding Seminar; 2021: 2021 International Conference of Interdisciplinary SciencesDO - 10.32503/prosidingseminar.v0i0.52, 2022)
Project-based learning has an advantage in which its stages are flexibly modified in accordance with course needs and goals. Thus, the flexibility of project-based learning stages provides a wide opportunity for language teachers to determine and design their own teaching stages before implementing them in the classroom. This article aims to describe the design of project-based learning in writing courses for college students, especially in the English language teaching. The participants are the writing lecturer, writing students, and the researcher itself. The research utilized a qualitative approach in which a single case study was employed. Data were collected through classroom observation, interview, documentation, and analyzed using descriptive analysis. The findings showed that, in general, the project-based learning in writing course covers four stages e.g. planning, designing, monitoring, and evaluating. Hopefully, the result of this research can be used as a guidance for lecturers who want to teach writing courses using project-based learning.